Unique colonoscopic manifestations in a patient with Henoch-Schönlein Purpura: a case report of an ileocecal valve ulcer - Tan, Haizhi; Xiao, Xiaobing; Deng, Jianrong (Frontiers in Pediatrics, 2025)
Ileocecal valve ulceration can arise from various causes, including infections, inflammatory bowel diseases, Behçet's disease, tumors and medications. We present a rare case of Henoch-Schönlein purpura (HSP)-associated ileocecal ulcer in a pediatric patient. The child initially presented with abdominal pain and subsequently developed extensive bilateral lower limb purpura on the third hospital day. Colonoscopic examination revealed erosions and shallow ulcerations localized to the ileocecal valve, with histopathological analysis revealing characteristic mucosal stromal edema and diffuse inflammatory cell infiltration. The patient exhibited marked clinical improvement following intravenous methylprednisolone pulse therapy. This case enriches the clinical spectrum of HSP and helps clinicians better understand its intestinal involvement.